ICRU report 91 on prescribing, recording, and reporting of stereotactic treatments with small photon beams: statement from the DEGRO/DGMP working group stereotactic radiotherapy and radiosurgery = ICRU-Bericht 91 über die Verschreibung, Aufzeichnung und Dokumentation von stereotaktischen Behandlungen mit kleinen Photonenfeldern : Stellungnahme der DEGRO/DGMP-Arbeitsgruppe Stereotaktische Strahlentherapie und Radiochirurgie - Wilke, Lotte; Andratschke, Nicolaus; Blanck, Oliver; Brunner, Thomas B.; Combs, Stephanie; Grosu, Anca-Ligia; Moustakis, Christos; Schmitt, Daniela; Baus, Wolfgang W.; Guckenberger, Matthias (Strahlentherapie und Onkologie, 2019)
The International Commission on Radiation Units and Measurements (ICRU) report 91 with the title “prescribing, recording, and reporting of stereotactic treatments with small photon beams” was published in 2017. This extensive publication covers different relevant aspects of stereotactic radiotherapy such as small field dosimetry, accuracy requirements for volume definition and planning algorithms, and the precise application of treatment by means of image guidance. Finally, recommendations for prescribing, recording and reporting are given.